A review on influencing factors, estimation methods, and improvement strategies for state of health in lithium-ion batteries - Wang, Bo; Wang, Xiaojuan; Hu, Bing; Xu, Lijun; Xiao, Yousufu (Journal of energy storage, 2025)
With the widespread application of lithium-ion batteries in electric vehicles, renewable energy storage, and portable electronic devices, State of Health (SOH) has become a critical metric for evaluating battery performance, lifespan, and safety. Over time, lithium-ion batteries inevitably experience capacity degradation and increased internal resistance, affecting their charging and discharging efficiency and safety. These issues directly impact the reliability and economic benefits of battery systems. By analyzing the factors influencing battery SOH, this paper explores the risks associated with SOH deterioration and comprehensively reviews current mainstream methods for assessing battery SOH. Special emphasis is placed on the necessity of multi-algorithm integration to enhance the accuracy of predicting battery health status. Additionally, measures to improve battery SOH are summarized. Drawing on existing literature, this paper also outlines the challenges and future directions for battery SOH prediction. Through a thorough review of lithium-ion battery SOH, this paper aims to assist researchers in gaining a deeper understanding of SOH deterioration causes and improvement strategies, thereby promoting the refinement of SOH assessment methods and the optimization of Battery Management Systems (BMS), providing valuable references for battery life prediction and maintenance. •Analyzed various influencing factors affecting the evolution of lithium-ion battery State of Health (SOH).•Elucidated the significance and benefits of a hybrid SOH assessment framework.•Investigated strategies to mitigate SOH degradation.•Outlined future prospects for SOH evaluation technologies.